Charlotte's web - Reynolds, Debbie; Lynde, Paul.; Gibson, Henry; Moorehead, Agnes, 1900-1974.; Hamner, Earl, Jr.; White, E. B. (Elwyn Brooks), 1899-1985.; Nichols, Charles, 1910-1992.; Takamoto, Iwao.; Barbera, Joseph; Hanna, William, 1910-2001.; Paramount Pictures Corporation; Hanna-Barbera Productions; et al. (Hollywood, CA : Paramount, 2006)
The story of Wilbur the pig and how, through his friendship with Charlotte the spider, he became famous and learned about life and death.
Videodisc release of the 1973 motion picture.
Based on the children's book by E.B. White.
Music and lyrics, Richard M. Sherman, Robert B. Sherman ; music arranger, Irwin Kostal.
Voices of: Debbie Reynolds, Paul Lynde, Henry Gibson, Agnes Moorehead.
MPAA rating: G.
DVD; NTSC, region 1; widescreen format; Dolby Digital mono.
Keywords: Swine -- Juvenile films; Spiders -- Juvenile films; Friendship -- Juvenile films; Animated films; Children's films; Musical films; Feature films; Fiction films; Film adaptations